Promoting the Concept of Saving in Early Childhood and Its Role in Developing Financial Awareness According to Saudi Vision 2030 - Aldossary, Norah Saleh Abdullah; Etman, Ali Abd Eltawab Mohamed; Omar, Sahar Mansour Sayed (Journal of Posthumanism, 2025)
The study aimed to identify the promotion of the concept of saving in early childhood and its role in developing financial awareness in accordance with the Kingdom’s Vision 2030. The study population and sample consisted of (109) kindergarten teachers in the city of Najran in the Kingdom of Saudi Arabia, who were randomly selected from government kindergarten institutions. The study was conducted during the second semester of the academic year (2024/2025). The descriptive analytical approach was used, as the study included a questionnaire directed to kindergarten teachers to determine the impact of kindergarten buildings in providing a supportive environment for developing economic concepts in children. The questionnaire included (14) paragraphs related to promoting the concept of saving in early childhood and its role in developing financial awareness in accordance with the Kingdom’s Vision 2030. The researchers used the theoretical framework, previous studies, and specialized experience in the field of kindergartens to develop the study tools. The results were processed using the SPSS statistical program, and the study reached the following conclusions: The positive role of kindergarten teachers in promoting the concept of saving in early childhood and its role in developing the child’s financial awareness from the point of view of kindergarten teachers. The results were generally positive for promoting the concept of saving in its various aspects.